Family and empowerment. A review of dengue from a social point of view - Valencia-Jiménez, Nydia Nina; Rodríguez-Triana, Zulema Elisa; Vélez-Álvarez, Consuelo (Universidad y Salud, 2021)
Introduction: Dengue prevalence in Central and South America requires comprehensive and contextualized interventions that ensure greater participation, responsibility, and awareness of the involved key players. Objective: To document scientific evidence on the role of family as a capacity-building environment in the prevention and control of dengue. Materials and methods: An integrative literature review was conducted through the search, selection, organization, and analysis of scientific articles published in Jstor, Scopus, Sciencedirect, Scielo and Pubmed databases during the 2015-2020 time period. The inclusion criteria were useful to select 20 articles. Results: The family is recognized as an important environment for human health care. Family’s participation, commitment, and empowerment constitute elements of interest for the design, implementation, and assessment of programs for the prevention and control of diseases such as dengue. Likewise, the need to incorporate comprehensive and contextualized approaches was identified. Conclusions: Families are fundamental for the construction of human capacities. Thus, they require support, motivation, improvement of living conditions, and acknowledegement of their natural ways of learning and teaching as an integrative strategy in social approaches to prevent and control dengue.